Arteriovenous malformations and headache. (January 2016) - Ellis, Jason A.; Mejia Munne, Juan C.; Lavine, Sean D.; Meyers, Philip M.; Connolly, E. Sander; Solomon, Robert A.
Highlights: Although it is a relatively uncommon pathological entity, brain AVM should be given consideration in the differential diagnosis for headache. An experienced medical team capable of a providing a multidisciplinary approach to headache management in patients with AVMs is ideal. AVM treatment with embolization, focal radiation, surgical resection, or a combination of these approaches can be safely performed and has the potential to completely eliminate associated headaches. Abstract: Brain arteriovenous malformations (AVM) are complex vascular lesions commonly associated with chronic headache. An occipital location appears to increase the risk of concurrent migraine-like headaches in AVM patients. We have experienced great success in treating these headaches through a multidisciplinary approach to eradicate cerebral AVM. However, the specific clinical characteristics of AVM-associated headaches and the most effective treatment strategies for these patients remain unclear. Here, we provide a comprehensive review of the literature on AVM-associated headaches. We detail the history, classification, epidemiology, presentation, pathophysiology, treatment options, and outcomes for this poorly described condition. Additionally, we illustrate our approach to the management of patients with occipital AVM and associated intractable headaches.